SEMANTIC AND MODEL PRINCIPLES OF LOGIC OF LAW - Гвоздік, О. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The semantic and model bases of logic of law by means of comparison of philosophical approaches are observed in the article.